MINING THE DATA USING GENETIC ALGORITHM AND THE CRITICAL EVALUTION OF THE ALGORITHM - SIVA PARVATHI DEVI B; CHAMUNDESWARI A 17
Feature selection is used as a preprocessing step to machine learning to remove noisy features.
PAPER BACK
PG